Prediksi Erosi dan Arahan Penggunaan Lahan Daerah Aliran Sungai Yeh Leh Provinsi Bali - Ni Made Ayu Ratna Sari; I Wayan Sandi Adnyana; I Nyoman Merit (Master Program of Environmental Science, Postgraduate Program of Udayana University, 2018)
Erosion in the watershed generally occurs due to land use that ignores the rules of soil and water conservation. There is much activity carried out by people living on land in the Yeh Leh watershed area, which makes the level of dependence is very enormous.The erosion forecast is using the USLE (Universal Soil Loss Equation) to estimate the erosion swift occurs and to obtain illustration in determining the precise soil and water measures in a region. The determination of land capability classification is using Arsyad’s method (1989) in which to classify the land ability by classifying the land ability class based on the value of land limiting factors, which then adjusted to the criteria of classification of land capability. The land use directional determination is applying the scoring method where combining field slope factor, soil sensitivity to erosion and daily rainfall intensity. The erosion level of the YehLeh watershed area is categorized as mild to very severe. A very light erosion level as large as 515 ha (21.01%), with the land use in the form of irrigated rice field and forest. The severe erosion level as large as 990.02 ha (40.40%) with land use in the form of plantations. The very heavy erosion level as large as 945.82 ha (38.59%) with land use in the form of plantations. The classification of land capability in the YehLeh watershed area consists of 5 classes of land abilities: class II of 115, 22 ha (4.70%), class III of 533.95 ha (21.79%), class IV of 423.61 (17.28%), Class VI of 1,102.03 ha (44.97%), and Class VII of 276.03 ha (11.26%), with some limiting factors for instance, soil texture, erosion and drainage. Proposed land use in the YehLeh watershed area use for forest areas is as protected forest of 456.49 ha (18.63%). Proposed land use outside of the forest area consist of 58.51 ha (2.39%) of seasonal crops, annual cultivation area of 990.02 ha (40.40%) and buffer area of 945.82 (38.59%). Keywords: watershed, erosion, land capability classification, proposed land use.